LINGUISTICS AND THE ENGLISH LANGUAGE INSTRUCTION - Hermawati Syarif (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
Linguistics as the scientific study of language has very crucial role in running language instruction. Changes in language teaching-learning  method reflect the development of linguistic theories. This paper describes how the three broad views of lingusitic theories, namely traditional grammar, generative grammar, and functional grammar work in relation to English language teaching and learning. Since both linguistics and language learning have the same subject to talk about, that is language, the knowledge of the language, then, is the core. Linguistics systematically discusses language as a whole, in which the universality of language is searched, as well as  particular language. Linguistic features analyzed are on the levels of Phonology, Morphology, Syntax, Semantics and Discourse as the basic components, supported by Psycholinguistics and Sosiolinguistics. In relation to language teaching and learning, especially English, such knowledge  on  the English language gives  learners the chance to apply in social communication  and in any ocassion. The use depends on the viewing of linguistic theories (English) in certain era, which reflects the need of learners in using English. It is assumed that the more linguistic competence someone has, the easier he/she can run his/her instructional activities. As the consequence, in the English language learning, the syllabus designer should  notify the mentioned levels of linguistic components while constructing English instructional materials, methods, and evaluation based on the stage of learners. Nevertheless, as the effect of using English as second language (L2) in certain countries, the varieties of English existed and the changes in particular elements of the language may appear that  result misunderstanding. In this case, English instructors/teachers should also update their linguistic competence, especially on Pshycholinguistic and Sociolinguistic points of view